Consumer vulnerability in pharmaceutical market: Case of Baltic countries - Melnikas, Borisas; Smaliukienė, Rasa (Journal of Business Economics and Management, 2007)
Consumer vulnerability receives attention in search for effective solutions of complex problems in the social welfare system on the international as well as local or regional scale. Pharmaceutical consumer vulnerability takes various forms and therefore it may be analyzed in social, economic, legal, ecological or purely medical terms. The article presents an integrated methodology that was applied to develop an indicator of pharmaceutical consumption and pharmaceutical consumer vulnerability; it also presents findings of the research, which employed this methodology to estimate vulnerability of different consumer groups as well as general consumer vulnerability in Lithuania, Latvia and Estonia. First Published Online: 14 Oct 2010